Advancements in additive manufacturing: Innovations in direct ink writing materials and their transformative practical applications - Kadirgama, Kumaran; Subramonian, Sivarao; Salleh, Mohd Shukor; Lee, Sara Kit Yee; Ramasamy, Devarajan; Mohamed Kassim, Anuar; U. K. Vatesh; Satish, Pujari; Dharsyanth R. (Taylor's University, 2024)
The domain of three-dimensional (3D) printing holds limitless potential, encompassing a diverse range of materials and applications. This review offers a comprehensive exploration of the Direct Ink Writing (DIW) technique within additive manufacturing, alongside recent breakthroughs in material advancement. The purview extends to encompass DIW methodologies, graphene oxide, hydrogels, shape-memory polymers, ceramics, polymers, and composite-based materials. The discussion delves into the multifaceted potential of 3D printing materials and their prospective applications, notably emphasizing the transformative role of DIW. The versatility of DIW is showcased in various fields, including energy storage, electronics, soft robotics, and biomedical applications. Through an in-depth analysis of capabilities of DIW and the diverse materials it encompasses, this review sheds light on the promising avenues that lie ahead in the evolving landscape of additive manufacturing.